Disturbance attenuation by output feedback for a class of nonlinear systems. (July 2016) - Wei, Chunling; Wang, Qiangde
This paper investigates the problem of disturbance attenuation by output feedback for a class of minimum-phase nonlinear uncertain systems with unknown control direction. In order to deal with the difficulties brought by the unknown direction, we first transform the original system into a new form by a linear state transformation. Then, based on a state observer, a constructive output feedback design procedure is proposed to solve the disturbance attenuation problem in the sense of L 2 -gain. The efficiency of the control method is demonstrated by a simulation example.